Interaction Effects between the Cumulative Genetic Score and Psychosocial Stressor on Self-Reported Drinking Urge and Implicit Attentional Bias for Alcohol: A Human Laboratory Study - Kim, Jueun (Alcohol Alcohol, 2019)
AIMS: The current candidate gene and environment interaction (cGxE) study examined whether the effects of an experimentally manipulated psychosocial stressor on self-reported drinking urge and implicit attentional bias for alcohol cues differ as a function of a cumulative genetic score of 5-HTTLPR, MAO-A, DRD4, DAT1 and DRD2 genotypes. The current study also examined whether salivary alpha-amylase level or self-reported anxiety state mediate these cGxE effects. SHORT SUMMARY: Individuals with high cumulative genetic risk score of the five monoamergic genotypes showed greater attentional bias toward alcohol cues when exposed to a psychosocial stressor than when not exposed. METHODS: Frequent binge-drinking Caucasian young adults (N = 105; mean age = 19; 61% male) completed both the control condition and stress condition (using the Trier Social Stress Test) in order. RESULTS: Regarding attentional bias, individuals with high and medium cumulative genetic risk scores showed greater attentional bias toward alcohol stimuli in the stress condition than in the control condition, whereas, those with low genetic risk scores showed greater attentional bias toward alcohol stimuli in the control condition than in the stress condition. No mediating roles of salivary alpha-amylase and anxiety state in the cGxE effect were found. Regarding self-reported drinking urge, individuals with high cumulative genetic score reported greater drinking urge than those with low genetic score regardless of experimental conditions. CONCLUSIONS: Although replication is necessary, the findings suggest that the association of a psychosocial stressor on implicit (but not explicit, self-reported) alcohol outcomes may differ as a function of the collective effects of five monoamine genes.